COMPARING CLASSICAL TEST THEORY AND ITEM RESPONSE THEORY FOR RESPIRATORY SYSTEM QUESTION INSTRUMENTS - Adha Nisfatulsanah; Bowo Sugiharto (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
This study aims to compare the results of instrument testing methods between applying classical test theory and item response theory using the Rasch model in question instruments on respiratory system material. This study employed descriptive quantitative methodology, with a sample involving 36 students. The analyzed instrument consisted of 40 multiple-choice questions on respiratory system material. Instrument analysis utilized classical test theory with Microsoft Excel and item response theory with Winstep Rasch ver 4.5.2.0. The data analysis from classical test theory and item response theory offers slightly different interpretations but is mutually complementary. Both classical test theory and item response theory may assess the validity, reliability, distractor effectiveness, difficulty level, and discriminating power of questions. Item response theory provides a comprehensive analysis of test results through the use of the Wright map as a bar which helps determine a student's ability about the difficulty level of the question. Scalogram is used to identify patterns in students’ responses, allowing for the detection of cheating and inaccuracies in answering questions. Additionally, DIF items are employed to identify item bias. This study concludes that any developed instrument must possess the characteristics that meet the requirements to measure competency effectively. The requirements for an instrument can be analyzed using item response theory with the Rasch model, which provides in-depth interpretation.Keywords: Classical test theory, item response theory, Rasch model, instrument